Influence of information credibility of Instagram posts on tourist decision-making behaviour - Chawla, Sayani; Sood, Ritu; Chawla, Amit (Journal of Tourism Management Research, 2024)
This research tries to identify the influence of Instagram posts on the decision-making behaviour of tourists. Social media plays a pivotal role in today’s travel and tourism environment. It also determines how people perceive and choose a destination. Social media acts as a platform for people to discuss and share about travel adventures, providing detailed information that can widely influence the decision-making process among visitors. Response to social media sharing and information credibility are the independent variables. Prior knowledge and tourist decision-making are the dependent variables. The research also studies the moderating role of the authenticity of social media posts in shaping tourists’ responses and choices. An online survey was conducted to collect primary data from 511 Delhi and the National Capital Region (NCR) respondents. The sampling design adopted was stratified random sampling. Analysis of moment structures (AMOS) was used to analyse the quantitative data collected. A structural equation modelling approach was used to analyse the data. The study reveals that Instagram and other platforms transform intangible aspects of destinations into tangible experiences, enriching tourists’ knowledge. Influencers and user-generated content play a crucial role in decision-making. The authenticity of the post plays a crucial role in shaping the tourist’s decision-making process.